Analisis Keamanan Komputer Terhadap Serangan Distributed Denial of Service (DDOS) - Hartini Ramli; Maharaja Yasin Alifsyah (PT. Global Research Collaboration, 2023)
Distributed Denial of Service (DDoS) is a type of active attack, an attack that can overwhelm a system by flooding a computer or server with network traffic, disrupting user services. The goal of this attack is usually to disable services and disconnect from the compromised computer or network. The impact is very large for companies or agencies that offer services. Victims of these attacks are unable to provide the services they are supposed to. Due to a bug or constraint on the server you are trying to use and one of the ways to deal with these attacks is to use a computer network firewall, which is useful for protecting computers from various outer space attacks. If the computer has a firewall security system, it is likely that no one on the Internet can access the data on the connected computer or web server. Firewall, works like a partition or wall that blocks the computer from the Internet. This